Three-Dimensional Printing Methods for Bioceramic-Based Scaffold Fabrication for Craniomaxillofacial Bone Tissue Engineering - Sheikh, Zeeshan; Nayak, Vasudev Vivekanand; Daood, Umer; Kaur, Anupreet; Moussa, Hanan; Canteenwala, Abbas; Michaud, Pierre-Luc; de Fátima Balderrama, Ísis [UNESP]; de Oliveira Sousa, Edisa; Tovar, Nick; Torroni, Andrea; Glogauer, Michael; et al. (MDPI, 2024)
Three-dimensional printing (3DP) technology has revolutionized the field of the use of bioceramics for maxillofacial and periodontal applications, offering unprecedented control over the shape, size, and structure of bioceramic implants. In addition, bioceramics have become attractive materials for these applications due to their biocompatibility, biostability, and favorable mechanical properties. However, despite their advantages, bioceramic implants are still associated with inferior biological performance issues after implantation, such as slow osseointegration, inadequate tissue response, and an increased risk of implant failure. To address these challenges, researchers have been developing strategies to improve the biological performance of 3D-printed bioceramic implants. The purpose of this review is to provide an overview of 3DP techniques and strategies for bioceramic materials designed for bone regeneration. The review also addresses the use and incorporation of active biomolecules in 3D-printed bioceramic constructs to stimulate bone regeneration. By controlling the surface roughness and chemical composition of the implant, the construct can be tailored to promote osseointegration and reduce the risk of adverse tissue reactions. Additionally, growth factors, such as bone morphogenic proteins (rhBMP-2) and pharmacologic agent (dipyridamole), can be incorporated to promote the growth of new bone tissue. Incorporating porosity into bioceramic constructs can improve bone tissue formation and the overall biological response of the implant. As such, employing surface modification, combining with other materials, and incorporating the 3DP workflow can lead to better patient healing outcomes.
Keywords: 3D-printing; bioceramics; bone tissue engineering; scaffold fabrication